Physical simulation test study on the stability of wading personnel in mine water inrush roadway - Qiang WU; Yi YAO; Yuanze DU; Huiping LI; Yingwang ZHAO; Hua XU; Shouqiang LIU; Xiao WANG (Meitan xuebao)
It is an important research content of emergency evacuation and rescue work to evaluate the hazard of personnel under the influence of multiple factors in mine water disasters. At present, the hazard judgment of people involved in water disasters mainly depends on experience, with certain blindness, but there are few reports on experimental research. Given this, a physical simulation test model for the stability of wading personnel in mine water inrush roadway was constructed, and mechanical monitoring of the cylinder model, standing stability of wading personnel, and wading speed testing were carried out under various flow conditions on different roadway gradients. Through the analysis of test data, the law of personnel wading stability and safety speed during the emergency escape of mine water disaster is extracted to reveal the potential relationship between personnel wading escape in mine roadway and roadway slope, water flow, and other factors. The experimental research results show that: ① In the mechanical monitoring test of the cylinder model, with the increase of the water level entering the roadway model, the average and maximum time of the monitoring force of the sensor at a height of 5 cm away from the slope are positively correlated; The mechanical monitoring values appear in a “band” mode, fluctuate up and down the mean level, and follow the approximate normal or normal distribution. The stretched state of the sensor at the height of 45 cm indicates that the human body may slip and lose stability under the action of roadway water flow; ② In the test of human standing stability, the difference in human standing stability is obvious under different standing posture in the same current condition, which indicates that the change of the effective area of the human body has a key and sensitive influence on the stability; ③ In the test analysis of people wading on 10°, 15° and 20° of roadway slope, when the average speed of people wading drops to about 0.2 m/s, it is very difficult for human body to stand wading, which can be called the safe speed threshold of wading. At the same time, the formula “upstream water level × fitted gradient + anhydrous velocity intercept” is proposed to characterize the linear negative correlation between the safe wading speed and the inlet water level, and the prediction function can be fitted; ④ A variety of tests were carried out on the roadway slope for personnel to walk uphill against water, downhill with water, slope without water, and downhill without water. Through statistical analysis of the data, the linear negative correlation between the slope against water and downhill with water and the slope of personnel on the roadway slope was revealed, and the formula of “slope × fitted gradient + horizontal velocity intercept” was proposed to determine the specific prediction function. The physical simulation test of the stability of wading personnel on the roadway in a mine water disaster is carried out to reveal the potential law of the stability and safety speed threshold of personnel wading evacuation, to promote the theoretical optimization and quantitative model research and development of intelligent water disaster emergency rescue, and provide scientific support for the study and construction of auxiliary decision-making of intelligent mine water disaster emergency rescue system.